Perancangan Aplikasi Perpustakaan Menggunakan Metode Spiral Dengan Netbeans - Ardiana; Muhammad Mustofa Ramadhan; Rizky Gimnastiar; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The library is an important tool in the world of education that allows students to access various learning resources. In educational institutions, a system is needed that can collect, manage, store, and distribute information. Therefore, the design of library applications is a necessary step to meet these needs. Through interviews and observations, researchers found several problems that needed to be addressed, including the absence of a specific application design in the library, the lack of use of technology that caused books to not be recorded properly, book searches that were done manually, and data processing that was still done manually. manual and prone to loss or damage. Therefore the method used in this study is the Spiral method, which is a popular software development method. This method breaks projects into smaller development cycles, emphasizing flexibility and adaptability to changes in complex software development. In this study, it has been concluded that the Spiral method is effectively used in designing library application systems because it allows for changes and adjustments at each stage. The built library application system has features that suit user needs and has succeeded in increasing the efficiency and productivity of library management. The implementation using the Java programming language and MySQL database was also successful. Thus, the development of library application systems using the Spiral method can provide effective and efficient solutions in library management. Subsequent developments can be carried out by adding features and regular updates to maintain the quality and reliability of the library application system.